2006
DOI: 10.1186/bf03353385
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary deposits of the 26 December 2004 tsunami on the northwest coast of Aceh, Indonesia

Abstract: The 2004 Sumatra-Andaman tsunami flooded coastal northern Sumatra to a depth of over 20 m, deposited a discontinuous sheet of sand up to 80 cm thick, and left mud up to 5 km inland. In most places the sand sheet is normally graded, and in some it contains complex internal stratigraphy. Structures within the sand sheet may record the passage of up to 3 individual waves. We studied the 2004 tsunami deposits in detail along a flowparallel transect about 400 m long, 16 km southwest of Banda Aceh. Near the shore al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(64 citation statements)
references
References 16 publications
3
58
2
1
Order By: Relevance
“…For instance, the thickness of the tsunami deposits, in the range of a few mm to approximately 40 cm and being approximately 10 cm on average, is very similar to those reported from the adjacent areas (Hori et al, 2007;Fujino et al, 2010), as well as from the other areas affected by the IOT (e.g., Moore et al, 2006) or other tsunamis (e.g., Gelfenbaum and Jaffe, 2003). This study found common features such as normally graded and massive layers.…”
Section: Iot Deposits Characteristicssupporting
confidence: 69%
See 1 more Smart Citation
“…For instance, the thickness of the tsunami deposits, in the range of a few mm to approximately 40 cm and being approximately 10 cm on average, is very similar to those reported from the adjacent areas (Hori et al, 2007;Fujino et al, 2010), as well as from the other areas affected by the IOT (e.g., Moore et al, 2006) or other tsunamis (e.g., Gelfenbaum and Jaffe, 2003). This study found common features such as normally graded and massive layers.…”
Section: Iot Deposits Characteristicssupporting
confidence: 69%
“…During the last 15 years, much effort has been devoted to documenting the various recent tsunami deposits (Nishimura and Miyaji, 1995;Sato et al, 1995;Shi et al, 1995;Dawson et al, 1996;Minoura et al, 1997;Bourgeois et al, 1999;Gelfenbaum and Jaffe, 2003;Nanayama and Shigeno, 2006;Higman and Bourgeois, 2008;Goto et al, 2011;Moore et al, 2011). The majority of these works focused on documentation of the 2004 Indian Ocean Tsunami (IOT) depositional effects along the coasts of Sumatra (Moore et al, 2006;Razzhigaeva et al, 2006;Richmond et al, 2006;Paris et al, 2007Paris et al, , 2009, Thailand (Hori et al, 2007;Kelletat et al, 2007;Choowong et al, 2008a, b;Matsumoto et al, 2008;Sawai et al, 2009;Fujino et al, 2010;Naruse et al, 2010), Sri Lanka (Morton et al, 2008), India (Bahlburg and Weiss, 2007;Srinivasalu et al, 2007) and Maldives (Kench et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Both types of impact were recently reported in relation to the catastrophic Sumatra tsunami in December 2004 (Liu et al, 2005;Synolakis and Kong, 2006;Jaffe et al, 2006;Moore et al, 2006;Goff et al, 2006). The effects of tsunami wave action will be very much influenced by the geomorphology of the coast and the material available for deposition.…”
Section: Tsunami Signatures In Terrestrial Coastal Environmentsmentioning
confidence: 99%
“…Moore et al (2006) provided a detailed description of sedimentary deposits along a 450 m transect south of heavily affected Lhok Nga (west of Banda Aceh): while soils were mostly scoured in the first ~50 m of impact along the transect (cf. Fig.…”
Section: Marine Sediment Deposition Salinisation and Vegetation Chanmentioning
confidence: 99%